Comparison of sliding mode controller application for buck-boost converter based on linear sliding surface - Lunde Ardhenta; Tri Nurwati (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
In the utilization of photovoltaic (PV), the output voltage produced is unstable because the conditions of irradiation received by PV is not uniform. Therefore, a direct current (DC) voltage converter is needed as an output voltage regulator. In this research, buck-boost converter is proposed to regulate the desired output voltage. The proposed controller in this research is a sliding mode controller (SMC) and employ a linear sliding surface to maintain the regulated voltage stable. This research was conducted by determining the component parameters and state space model of the buck-boost converter. Proportional integral derivative (PID) controller with integral of time-weighted absolute error (ITAE) method is used as a comparison of the proposed method. The performance results were observed from the buck-boost converter by performing 3 fault scenarios, variation in supply voltage, resistor in load side, and the desired output voltage. The results obtained of SMC has a faster settling time than PID controller. The voltage deviation of buck-boost converter exhibits that SMC is smaller than the PID control. In addition, under some experiment conditions, the PID control could not or did not fit in some scenarios while the output control values of SMC matched the changes in the entire scenarios.